Error Analysis in Using Simple Past Tense Found in Students’ Writing of Recount Text - Tira Nur Fitria (Ahmad Dahlan Journal of English Studies, 2020)
This research was to find out the types of error analysis and the most dominant type of error analysis found in Students’ Writing Composition in simple past tense especially in Recount Text. This study used a mixed-method, both qualitative and quantitative approach. From the analysis, the students’ error in writing composition of simple past tense consists of some aspects of writing, they were in grammar, punctuation and spelling. In grammar, there were 57 data or 53.37 %, which consist of errors in class words like in determiner/article (25 data or 43.86 %), in verb (14 data or 24.56 %), in preposition (11 data or 19.30 %) and the last in noun (7 data or 12.28 %). While, the most dominant error was in the determiner/article. Second, in the aspect of spelling, there were 26 data or 21.70 %). Third, in the aspect of punctuation, there were (23 data or 24.53 %). Based on the frequency of each aspect of error, the most dominant error found in students’ writing composition was in the aspect of grammar as 57 data or 53.37 %.